Intensive exposure to narrative in story books as a possibly effective treatment of social perspective-taking in schoolchildren with autism - Tsunemi, Kohei; Tamura, Ayana; Ogawa, Shino; Isomura, Tomoko; Masataka, Nobuo (Frontiers in Psychology, 2014)
One of the major characteristics of autism is impairment of communication and socialization. While such impairment per se has been well documented, research into effective interventions for children with this developmental disorder is still limited. Here we present preliminary evidence for the possibility of improvement of the capability of social perspective-taking in schoolchildren with autism by having intensive experience with narrative, in which they were exposed to narrative in storybooks read by their parents over a consecutive 5- to 6-day-period. When their capability was evaluated on the basis of a conventional role-taking task, the mean score tended to increase after the exposure as compared to before the exposure, whereas such a change was not recorded in children who did not experience such exposure. These effects were confirmed when the children were retested 4 months later. Although preliminary, the current study represents a step toward the development of more effective social perspective-taking interventions for children with autism.